How the ownership structure and firm size effect on intellectual capital disclosure? A case study before and during COVID-19 - Paramita, Putu Winda Agastya; Mimba, Ni Putu Sri Harta; Gayatri, Gayatri; Wirajaya, I Gde Ary (International research journal of management, IT and social sciences, 2023)
This study aims to identify, analyze and obtain empirical evidence regarding the effect of ownership structure consisting of managerial ownership, institutional ownership and foreign ownership as well as firm size on intellectual capital disclosure before and during COVID-19. In addition, this study also tests whether there are differences in intellectual capital disclosures made before and during Covid-19. The sample in this study were banking sub-sector companies listed on the Indonesia Stock Exchange in 2018-2021 which were divided into two groups, namely before COVID-19 and during COVID-19. This study adopts the ICD In model from Ulum (2015) which has been modified by adding several items that are in accordance with applicable regulations in Indonesia. The data analysis technique used was multiple linear regression and paired sample t-test for different tests using evies 12 student version software. The results of the study show that prior to COVID-19 managerial ownership, institutional ownership and foreign ownership had no effect on intellectual capital disclosure. Firm size had a positive effect on intellectual capital disclosure before COVID-19. During COVID-19, managerial ownership had a negative effect, institutional ownership had a negative effect and foreign ownership had no effect on intellectual capital disclosure.